Diastereoselective Synthesis of Chiral Bicycle Phosphoramides Derived from (S)-2-(Anilinomethyl) pyrrolidine - El-Hendawi, H.M.; Barrisford, D.J.; Baraka, R.M.; El-Nehhal, I.M. (Asian Journal of Chemistry, 2010)
The diastereoselectivity of the chiral bicyclic phosphoramide synthesis can be improved under certain conditions of temperature and degree of polarity of the solvent. Measured diastereomer ratio (exo-isomer : endo-isomer) enhanced from (1.00 : 1.00) to (1.00 :1.44) in favourable cases. This enhancement in the diastereoselectivity is highly relevant to the development of asymmetric synthesis, where chiral bicyclic phosphoramides are used as catalysts.